Energy-harvesting materials based on the anomalous Nernst effect - Mizuguchi, Masaki (Sci Technol Adv Mater, 2019)
The anomalous Nernst effect (ANE), one of the thermomagnetic effects studied for a long time, has recently attracted renewed attention. The ANE, which originates from fictitious fields in momentum space, is essential for clarifying the interplay among heat, spin, and charge in magnets. Moreover, compared to the Seebeck effect, it has various benefits for application to high-efficiency energy-harvesting devices as it may provide much more simple lateral structure, higher flexibility, and much lower production cost. In this review, we discuss various topics related to the methods to modulate the ANE for its thermoelectric applications. In addition, we review strategies to design materials to obtain large ANE including Weyl magnets and thermoelectric devices for effectively utilizing the ANE.